AGIHAN SPASIAL POTENSI AIRTANAH BERDASARKAN KRITERIA KUALITAS DI CEKUNGAN AIRTANAH PALU PROVINSI SULAWESI TENGAH - Zeffitni, Zeffitni (MEKTEK, 2010)
The water supply trend to decrease of quantitatively and qualitatively, meanwhile the water demand,therefore problem to manage of water resources exist. This phenomenon also happened at PaluGroundwater Basin Central Sulawesi Province. Distribution of groundwater are spatial and temporalcausing the water supply requirements for domestic in Palu City is not all fulfilled. This study aimed toanalyze groundwater potency zone based on the quality criteria.The research are laboratory analysis for groundwater quality and spatial analysis for distribution ofgroundwater quality. The research evaluation are hydrochemical for drinking water. The research methodsfor sample base : SNI. 6989.58: 2008. ICS 13.060.50 the methods of groundwater sampling. The researchevaluation based on analyzing chemical parameters: pH, TDS, Fe, Mn, Cl, NO3, NO2, and SO4.The research finding that spatial distribution of groundwater in east and west Palu Groundwater Basin withlimit Palu River. The analysis result of chemical parameters for drinking water based on Permenkes.No.907/MENKES/SK/VII/2002, that the potential level of groundwater quality in good class and can be usedfor drinking water